Divided they stand: Hollywood unions in the information age. (1st January 2007) - ,; ,
Abstract : In an effort to increase labour power, trade unions representing communications and creative workers in North America have pursued a form of convergence, merging with each other and restructuring themselves along similar lines to their employers. This paper examines the issues surrounding labour convergence by taking up the failed merger between the Screen Actors Guild and the American Federation of Television and Radio Artists. It finds that, although the leaders of both unions supported the merger, the particular characteristics of the unions, including their culture, sense of craft identity and the lived experience of members, derailed the effort.